Variation in Coarse Particulate Matter (PM10) and Its Characterization at Multiple Locations in the Semiarid Region - Zeb, Bahadar; Alam, Khan; Ditta, Allah; Ullah, Sami; Ali, Hayssam M.; Ibrahim, Muhammad; Salem, Mohamed Z.M. (Frontiers in Environmental Science, 2022)
Introduction: The elemental composition and morphological study of particulate matter are very important to understand the nature of particles influencing the environment, climate, soil, and health. Methods: The PM10 samples were collected during the winter season (2018) in Nowshera city, KPK, Pakistan, in three locations, namely, urban, industrial, and suburban. Scanning electron microscopy (SEM) and electron-dispersive X-ray (EDX) spectroscopy were used to examine the PM samples for morphological examination and elemental composition. Results: The average mass concentrations of particulate matter (PM10) at the urban, industrial, and suburban locations were 238.5, 505.1, and 255.0 μg m−3, respectively. The average PM10 mass concentration was higher than the WHO and National Ambient Air Quality Standards (NAAQS). The results of EDX showed that samples contained variable amounts of thirteen elements, such as oxygen, carbon, silicon, magnesium, sodium, calcium, iron, aluminum, potassium, sulfur, titanium, gold, and chlorine. The probable sources of PM were biogenic like plant debris, pollen, and diatoms; geogenic like road dust and resuspended soil dust; and anthropogenic like carbonaceous particles and fly ash, as confirmed by SEM–EDX. The carbonaceous species, that is, OC and EC, had average values of 55.8 ± 13.1 and 4.6 ± 0.6, 5.2 ± 3.2, and 36.4 ± 10.4, 40.0 ± 2.6 and, 6.3 ± 0.2 in industrial, urban, and suburban locations, respectively. Similarly, OC/EC had average values of 12.0 ± 1.2, 8.0 ± 3.0, and 6.3 ± 0.2 in industrial, urban, and suburban locations, respectively. Highly significant correlations among water-soluble ions (K+), OC, and EC were found in each location. Conclusions: The examined PM10 mass concentration in Nowshera city was above the thresholds of National Ambient Air Quality Standards (NAAQS) set by the U.S. Environmental Protection Agency (EPA). In addition, the concentration of pollutants was the highest at the industrial site compared to the other sites. The HYSPLIT model showed that the air mass originated from local sources like cement industries, brick kiln industries, and others.